Country Music Goes to War - Wolfe, Charles K. (Book collections on Project MUSE., 2015)
""Listening to the Beat of the Bomb"" UPK author Charles Wolfe discusses his work and his new book Country Music Goes to War in the NEW YORK TIMES. While Toby Keith suggests that Americans should unite in support of the president, the Dixie Chicks assert their right to criticize the current administration and its military pursuits. Country songs about war are nearly as old as the genre itself, and the first gold record in country music went to the 1942 war song ""There's a Star Spangled Banner Waving Somewhere"" by Elton Britt. The essays in Country Music Goes to War demonstrate that country m.